Brand identity essentials 100 principles for designing logos and building brands - Budelmann, Kevin; Kim, Yang 1968-.; Wozniak, Curt. (Beverly, Mass. Rockport Publishers, 2010)
This title outlines and demonstrates basic logo and branding design guidelines and rules through 100 principles including the elements of a successful graphic identity, identity programs and brand identity, and all the various strategies and elements involved.
Imagery -- Color -- Dimension -- Contrast -- Shape -- Symbols -- Typography -- Writing -- Story -- Order -- Variation -- Personalization -- Psychology -- Process -- Production -- Digital identity -- Trends -- Shortcuts -- Social media -- Multiples -- Intellectual property -- Documentation -- Evolution -- Competition -- Originality -- Wit-- Idealism -- Authenticity -- Commitment -- Strategy -- Research -- Touchpoints -- Inspiration -- Simplicity.
Includes index.
Keywords: Logos (Symbols) -- Design; Industrial design coordination